Agreement between 2 SS-OCT biometry devices. Issue 10 (October 2022) - McLintock, Cameron; Niyazmand, Hamed; Seo, Shiney; Barrett, Graham; Nilagiri, Vinay Kumar; McKelvie, James
Abstract : A prospective study assessing the agreement between 2 swept-source optical coherence tomography ocular biometers found statistically and clinically significant differences for posterior and total corneal metrics. Abstract : Purpose: To assess the agreement between 2 swept-source optical coherence tomography biometry devices, Anterion and IOLMaster 700. Setting: Tertiary referral center, Brisbane, Australia. Design: Prospective comparative study. Methods: Bland-Altman analysis was used to assess agreement between devices for flat (K1), steep (K2), and mean (Km) keratometry for anterior, posterior, and total cornea, lens thickness (LT), anterior chamber depth (ACD), central corneal thickness (CCT), white to white (WTW), and axial length (AL). Generalized estimating equations were used to control for within-patient between-eye correlations. Interdevice differences were considered clinically significant if they were likely to alter the spherical refractive outcome by 0.25 diopter (D) or more. Results: 159 eyes of 91 patients (41 male, 50 female) were included. Statistically significant differences were found for K1, K2, and Km for anterior, posterior, and total cornea. When the Anterion was compared with the IOLMaster 700, the mean differences were as follows: anterior K1: −0.17 D, anterior K2: −0.18 D, anterior Km: −0.17 D, posterior K1: −0.38 D, posterior K2: −0.36 D, posterior Km: −0.37 D, total K1: −0.65 D, total K2: −0.82 D, and total Km: −0.74 D. The difference in posterior and total K metrics was clinically significant. Statistically significant differences were noted for LT: 0.159 mm, CCT: −0.004 mm, ACD: 0.054 mm, and WTW: −0.152 mm, although these were not found to be clinically significant. There was no significant difference between devices for AL. Conclusions: This study found statistically and clinically significant differences for both posterior and total keratometry between the Anterion and the IOLMaster 700. Posterior and total corneal parameters cannot be considered interchangeable between devices.